Community Participation Level Model for Community forest Management in Klongtagrao Watershed Area, Chachoengsao Province - Permpul , Kittipot; Tantanasarit, Sittichai (วารสารวนศาสตร์ไทย, 2022)
Influence of deterministic factors education on the community participation level for community forest management in Klongtagrao watershed, Thatakieb district, Chachoengsao province was studied in five villages of which community forests were as follows: Nhongkhayang, Romphothong, Thammaratnai, Kao-krating and Khao-klouymai village. Eighteen factors expected to have influence on the community participation level were determined. It was divided into each community mean, including 225 sampling families including with measurement tri-dimensions of the participation as follows: quantitative, qualitative and transferring dimension by assessment the level of the participation from three resources, namely outsider experts, the leader’s community working management for community forests and deep interview together with observation of the researcher then they were averaged and studied the correlation. It was found that there were nine factors relating to the level of participation. That was the amount of data information about community conservation received, understanding towards data, interest towards data, the ability communication inside the community, the potential of formal leaders, the potential of informal leaders, the potential of all leaders in the community, conservative way of life, and trendy of conservation. The proper equation was chosen by stepwise analysis with alpha in/out 0.1. It was found the suitable equation for predicting the level of participation was Community participatory level (CPL) = -58.91 + 1.46 leader potential R2(adj) 0.79, Quantitative CPL = -53.00 + 1.92 leader potential; R2(adj) 0.89, Qualitative CPL = -57.35 + 2.00 leader potential; R2(adj) 0.80, and Transferring CPL = -54.6 + 1.75 formal leader potential; R2(adj) 0.80 Keywords: Community participation level, Community forest, Klongtagrao watershed